Description and search: metadata as infrastructure - Buckland, Michael K. (2007)
The first and original use of metadata is for describing documents. XML, the Dublin Core and MARC library catalog records are examples. The name "metadata" (beyond or with data) and the popular definition "data about data" is based on this use. A second use of metadata is to form organizing structures by means of which documents can be arranged. These structures can be used both to search for individual documents and also to identify patterns within a population of documents. The second role of metadata involves an inversion of the relationship between document and metadata. These structures can be considered infrastructure.